Association of Pharmacist Prescription of Hormonal Contraception With Unintended Pregnancies and Medicaid Costs. Issue 6 (June 2019) - Rodriguez, Maria I.; Hersh, Alyssa; Anderson, Lorinda B.; Hartung, Daniel M.; Edelman, Alison B.
Abstract : OBJECTIVE: To estimate unintended pregnancies averted and the cost effectiveness of pharmacist prescription of hormonal contraception. METHODS: A decision-analytic model was developed to determine the cost effectiveness of expanding the scope of pharmacists to prescribe hormonal contraception compared with the standard of care and contraceptive access in clinics. Our perspective was that of the payor, Oregon Medicaid. Our primary outcome was unintended pregnancies averted. Secondary outcomes included: costs and quality-adjusted life years (QALYs). Model inputs were obtained from an analysis of Medicaid claims for the first 24 months after policy implementation in Oregon, and the literature. Univariate and bivariate sensitivity analyses, as well as a Monte Carlo simulation, were performed. RESULTS: Among Oregon's Medicaid population at risk for unintended pregnancy, the policy expanding the scope of pharmacists to prescribe hormonal contraception averted an estimated 51 unintended pregnancies and saved 1.6 million dollars. Quality of life was also improved, with 158 QALYs gained per 198, 000 women. Sensitivity analysis demonstrated that the model was most sensitive to the effect on contraceptive continuation rates. If contraceptive continuation rates among women receiving care from a pharmacist are 10% less than among clinicians, than pharmacist prescription of hormonal contraception will not avert unintended pregnancies. CONCLUSION: Pharmacist prescription of hormonal contraception averts unintended pregnancies and is cost effective. Full implementation of the policy is needed for maximum benefits. Prospective data on the effect of the policy on contraceptive continuation rates are needed. Abstract : Pharmacist prescription of hormonal contraception is a cost-effective strategy for Medicaid to avert unintended pregnancy.